Improvement of trapping performance of magnetic particles by magnetic multi-poles via Brownian dynamics simulations of magnetic rod-like particles in a Hagen-Poiseuille flow. (3rd June 2022) - Yamanouchi, Takeru; Satoh, Akira
Abstract : In the present study we have implemented a Brownian dynamics simulation of a Hagen-Poiseuille flow in a cylindrical vessel and have investigated the feasibility of multi-pairs of magnetic poles for exhibiting a good particle trapping performance. We have focused on two representative types of configuration consisting of two pairs of magnetic poles. The first is a vertical configuration of two pairs of poles arranged perpendicular to the direction of the flow field. The second is a parallel configuration, where each pair of magnetic poles is arranged along the surface of the vessel wall. In the case of the vertical pole arrangement, although densely-packed aggregates were formed between the poles, their location was unstable in the flow field and they tended to be carried away downstream. In contrast, a densely-packed cluster formed in the parallel arrangement tended locate in a more stable manner along the surface of the wall where the flow field is weaker. We conclude that under appropriate conditions of the magnetic particle-particle interaction strength, the applied magnetic field strength and the pole separation distance, the parallel arrangement of magnetic poles is the configuration of choice for giving rise to a superior trapping performance. GRAPHICAL ABSTRACT: UF0001